Comparison of the 5-Year Outcomes Between Standard and Short Fit-and-Fill Stems in Japanese Populations - Suguru Kato, MD; Masahiko Nozawa, PhD; Sungon Kim, PhD; Yuko Sakamoto, PhD; Hironori Ochi, PhD; Muneaki Ishijima, PhD (Arthroplasty Today, 2022)
Background: Fit-and-fill stems are known to have excellent outcomes; however, severe stress shielding has been reported in Japanese populations. Short fit-and-fill stems were modified for Asians; however, there have been no previous reports of its outcome. In this study, we compared the 5-year (mean 68-month) outcomes of 2 fit-and-fill stems with different lengths (standard or short). Material and methods: We reviewed 100 total hip arthroplasties in each standard- or short-stem group. Radiographs were evaluated for femoral morphology, stress shielding, bone remodeling, and fixation. Clinical evaluation was performed using the Japanese Orthopaedic Association (JOA) scores. Results: There was no difference in the degree of stress shielding between the 2 groups. Significant differences were observed in radiolucent lines in zone 4 (P = .005) and cortical hypertrophy in zone 3 (P < .0001) and 5 (P = .048) between the 2 groups. The canal flare index (P < .0003), cortical index (P < .0003), height (P < .0345), and stem size (P < .0081) individually affected stress shielding in the standard-stem group. In contrast, the cortical index (P < .0107) was the only relative factor in the short-stem group. All stems were judged to have bone ingrowth. The JOA score improved significantly (P < .0001); however, there were no significant differences between the 2 groups. Conclusion: The outcomes of both standard and short fit-and-fill stems were favorable. There were no significant differences in the stress shielding or JOA scores. Although there were a few differences in bone remodeling and factors affecting stress shielding, stem length reduction has been achieved without adverse effects with the Japanese femur.